PENGARUH KOMPLEKSITAS, OPINI AUDIT, SOLVABILITAS, UKURAN KANTOR AKUNTAN PUBLIK, DAN PANDEMI COVID-19 TERHADAP AUDIT DELAY - Anita Muliani (2021)
This research aims to prove empirically the influence of complexity, audit opinion, solvency, size of public accounting firms, and the covid-19 pandemic against audit delays in property and real estate sector companies in the period 2018-2020. The research is quantitative research that uses secondary data to obtain the required data, namely annual reports and financial statements audition. In this study, the sample used was as many as 49 companies using purposive sampling techniques using established criteria. Techniques used in analyzing data are, regression model selection test, classical assumption test, hypothesis test, and panel data regression using STATA software version 16. Based on the results of the analysis of the data that has been presented, it can be concluded that 1) the operating segment has no effect on audit delays; 2) subsidiaries positively affect audit delays; 3) Audit opinion negatively affects audit delay; 4) solvency negatively affects audit delay; 5) KAP size has no effect on audit delay; and 6) the covid-19 pandemic had a significant positive effect on audit delays.